2019
DOI: 10.1186/s41240-019-0130-7
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of autochthonous probiotic bacterium and Mentha piperita diets in Catla catla (Hamilton, 1822) for enhanced growth and immune response

Abstract: Two dietary experiments were performed to evaluate the impact of the herb Mentha piperita as a dietary supplement on Catla catla. In Experiment 1, fingerlings (0.45-2.60 g) were fed on diets supplemented with M. piperita at different levels (P1, P2, P3, and P4 at 2, 4, 6, and 8 g Kg −1 of feed) and C1 served as the control with no peppermint supplementation. In Experiment 2, fingerlings (0.40-3.15 g) were fed with diets containing autochthonous probiotic bacteria Bacillus coagulans (3000 colony forming unit g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…This might be associated with the existence of probiotic bacterium incorporated in diet which replaced the brutal microbial promoters (Sun et al 2010) or might be due to establishment of probiotic bacteria in gut of fishes that extended its exogenous enzyme production conclusively enhancing the growth performance (Bhatnagar et al 2012;Bhatnagar and Lamba, 2017). Similar results were achieved by Bhatnagar and Saluja (2019) in which high growth performance were observed in C. catla fingerlings when fed on Mentha piperita supplemented diet at the rate of 6 g kg −1 along with probiotic bacterium B. coagulans @ 3000 CFU g −1 of feed. FCR was found to be significantly low in dietary treatment G3 in those group of fingerlings which fed on Z. officinale-supplemented diet which clearly suggested that Z. officinale performed as efficient appetizer and thus fingerlings utilized the Z. officinale-supplemented diet effectively which subsequently increased the digestibility.…”
Section: Discussionsupporting
confidence: 81%
“…This might be associated with the existence of probiotic bacterium incorporated in diet which replaced the brutal microbial promoters (Sun et al 2010) or might be due to establishment of probiotic bacteria in gut of fishes that extended its exogenous enzyme production conclusively enhancing the growth performance (Bhatnagar et al 2012;Bhatnagar and Lamba, 2017). Similar results were achieved by Bhatnagar and Saluja (2019) in which high growth performance were observed in C. catla fingerlings when fed on Mentha piperita supplemented diet at the rate of 6 g kg −1 along with probiotic bacterium B. coagulans @ 3000 CFU g −1 of feed. FCR was found to be significantly low in dietary treatment G3 in those group of fingerlings which fed on Z. officinale-supplemented diet which clearly suggested that Z. officinale performed as efficient appetizer and thus fingerlings utilized the Z. officinale-supplemented diet effectively which subsequently increased the digestibility.…”
Section: Discussionsupporting
confidence: 81%
“…Hamka et al (2020) [12] reported that the use of a combination of Bacillus megaterium PTB 1.4 and Pediococcus pentosaceus E2211 through a fish feed provided better performance than the single use of either of the two probiotics. The combined use of probiotics (Bacillus coagulans) and plant extract (Mentha piperita) ensured better growth performance, nutrient retention and immunity in Catla as compared to a singly application (Bhatnagar and Saluja, 2019) [3] .…”
Section: B) Administration Of Probiotics Singly or In Combinationmentioning
confidence: 99%
“…Lactobacillus plantarum N11 and B. velezensis H3.1 were both combined with Nile tilapia (Oerochromis niloticus) to promote a higher survival rate (583.33%) when compared to the single application of L. plantarum (54.17%) and B. velezensis (41.67%) (Doan et al, 2018). Combined application of B. coagulans and Mentha piperita in Catla catla improved growth performance, nutrient retention, and immunity (Bhatnagar and Saluja, 2019).…”
Section: Single and Combinationmentioning
confidence: 99%